Gambaran Kualitas Hidup Perempuan Yang Menikah Diusia Dini Di Desa Sumampeno Kecamatan Wakorumba Utara Kabupaten Buton Utara Tahun 2023 - Rahma Fanti; Ruslan Majid; Hartati Bahar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Word Health Organization (WHO) Early marriage is a marriage carried out by a couple or one of the partners is still categorized as a teenager under 19 years of age. The aim of this research is to describe the quality of life of women who marry at an early age in Sumampeno Village, North Wakorumba District, North Buton Regency. This research is qualitative research with a phenomenological approach. The informants in this research consisted of 2 main informants, namely women who married at an early age, 2 key informants, namely female family members who married at an early age, and 1 supporting informant, namely the Head of Sumampeno Village. The data collection technique is by in-depth interviews and then the data is analyzed using the content analysis method. The physical domain of all informants felt pain. The sleep quality of all informants had poor sleep quality. The psychology domain, namely negative feelings, all informants experienced negative feelings. Body image/appearance means that all informants do not like their current body shape because of changes in body shape.